THE STUDENTS IN THE SOCIAL SPACE OF A BIG CITY: THE RESULTS OF A SOCIOLOGICAL STUDY - P. A. Ambarova; N. V. Shabrova (Высшее образование в России)
The article presents the results of a sociological study of the role of university students in the formation of the cultural and educational space of the Urals megalopolis. The authors reveal the socio-cultural, personnel, economic, managerial, image functions of universities, show the relationship between the social resource ofa large city and the resource ofstudents as a key educational community of universities. The empirical basis of the article is the materials of focus groups and a questionnaire survey conducted among university students in Ekaterinburg. The purpose of the article was to reveal the possibilities and problems of integration of students as an educational community in the structure of the urban community. The research tasks were to reveal: 1) the students' opinions about the importance of university and higher education communities in the the urban community life; 2) the degree of students' awareness of the cultural and educational resources of the city; 3) the peculiarities ofthe positioning of universities in the urban life space.